A difference of perspective? Māori Members of Parliament and te ao Māori in Parliament. (1st December 2016) - White, Te Hau
Abstract : This article will aim to determine the form and place of te ao Māori in the New Zealand Parliament. The article will analyse the maiden speeches of 12 Māori Members of Parliament from across the political spectrum and from different Parliaments since the adoption of Mixed Member Proportional Electoral System in 1996, and will investigate their commitment to te ao Māori based on deductive and inductive discourse analysis. It seeks to determine the presence of Māori identity indicators, as well as to determine themes unique to the Māori political context. The election of the 51st New Zealand Parliament was noted as having the greatest representation of Māori of any parliament in New Zealand history. Of the 121 Members of Parliament, 26 identify as Māori or as having Māori heritage. However, while the number of Māori Members of Parliament has increased, this does not provide the full picture of Māori representation in Parliament. This article will ask 'How do Māori Members of Parliament best represent te ao Māori in the New Zealand Parliament?'. The research considers how Māori Members of Parliament 'represent' Māori in the debating chamber in Parliament, specifically, to what extent these Members of Parliament represent te ao Māori. This research also asks whether substantive representation of te ao Māori varies across the electorate types, Māori, general and list seats. The research seeks to provide qualitative analysis of the presence of te ao Māori in Parliament and which Members of Parliament most often represent a Māori worldview. Both descriptive and substantive representation provide the means for a minority perspective to be present within a parliament.